Botrychium dusenii (H.Christ) Alston (Ophioglossaceae) nueva adición para la flora vascular del Parque Nacional Pali Aike, Región de Magallanes, Chile - DOMÍNGUEZ, ERWIN; SUAREZ, ÁNGEL; BAHAMONDE, NELSON; OPAZO, SERGIO (Gayana Botánica, 2011)
We report the presence of Botrychium dusenii (H. Christ) Alston (Ophioglossaceae), collected for the first time in the Pali Aike National Park, increasing to two cited pteridophytes for this protected area. This finding extends the distribution range of this species towards the Patagonian Steppe.